Barriers to preventive care: analyzing the socio-ecological determinants of cardiovascular health in pregnant women - Cynthia L. Fok; Saanie Sulley; Alicia Aroche; Deidre McDaniel; Deborah Frazier (Discover Public Health)
Abstract Background Cardiovascular disease (CVD) is one of the leading causes of maternal mortality. As such, the provision of clinical preventive services during pregnancy among women with CVD risk factors, such as hypertension, obesity, and diabetes, can mitigate the risk for later-life CVD. However, the provision of clinical preventive services are suboptimal among women of reproductive age. Therefore, we sought to investigate the sociodemographic differences in the provision of services among pregnant women with CVD risk to identify gaps in care and missed opportunities for preventing CVD during pregnancy. Methods We performed a retrospective analysis of the National Ambulatory Medical Care Survey (NAMCS) data for women aged 15–44 at risk for CVD between 2014 and 2019. Patients at risk for CVD were classified based on prior diagnoses of obesity, hypertension, diabetes, and hyperlipidemia. Preventive clinical services include education on diet/nutrition and exercise, as well as screening for blood pressure and glucose. Multivariate logistic regression models assessed the relationship between pregnancy status and preventive service receipt, while controlling for demographic factors. Results 2289 patients at risk for CVD were included in this study; among them, 486 were pregnant and 1803 were not pregnant. Pregnant women were less likely than non-pregnant women to receive preventive clinical services, except for glucose screening (aOR:1.79; 95% CI: 0.88–3.63). Among pregnant women, non-Hispanic Black and Hispanic/Latine women were less likely to receive exercise counseling and a glucose test. Furthermore, women ages 35–44 were less likely to receive blood pressure (aOR: 0.10; 95% CI: 0.02–0.54) and glucose (aOR: 0.42; 95% CI: 0.10–1.73) tests. Conclusions This study provided insight into the provision of clinical preventive services among pregnant populations at risk for CVD. Study findings revealed missed opportunities in addressing CVD risk during pregnancy, especially among non-Hispanic Black and Hispanic/Latine women as well as those 35 and older. These findings merit the need for more community- and clinical-level interventions in order to address the gaps in comprehensive preventive care among pregnant women with CVD risk.